FIGURATIVE LANGUAGE IN AMIR HAMZAH’S POEMS - Novia Khairunisa; I Wy Diergeyasa; Citra Anggia Putri (State University of Medan, 2020)
This study dealt with figurative language in Amir Hamzah’s selected poems. The objective of this study were to investigate the types of figurative language found in Amir Hamzah’s selected poems and to find out the literal meaning of figurative language found. This study was conducted by using qualitative method to solve the problems. The data of this study were phrases and sentences contained figurative language in the poems. The sources of data were six poems poems which had multiple series taken from Amir Hamzah’s Poetry Anthology of Buah Rindu. The data were selected by using random sampling technique. For collecting the data, this study used documentary technique, and the instruments of data were documentary sheets. The data were analyzed by using descriptive qualitative method. The findings of this study are there twenty two figurative languages found as follows, three figurative language of metaphor (13.63%), seven figurative language of hyperbole (31.81%), five figurative language of personification (22.72%) and seven figurative language of simile (31.83%). The literal meaning of figurative language found in Amir Hamzah’s poems were basically was about the love story of Amir himself and also talking about his longing to his mother.Keywords : Figurative Language, Figure of Speech, Poem